Glycyrrhiza uralensis extract supplementation mitigated the negative effects of prolonged low-dose exposure to Deoxynivalenol and Zearalenone on growth performance and intestinal health of broiler chickens - Chen, Yan; Zhang, Guohua; Li, Jiawei; Li, Ximei; Jiang, Susu; Zha Xi, Yingpai; Guo, Yanli; Lu, Jianxiong (Frontiers in Veterinary Science, 2025)
Deoxynivalenol (DON) and Zearalenone (ZEN), common symbiotic mycotoxins found in mold-contaminated cereal feed, adversely affect broiler’ health. Glycyrrhiza uralensis has various pharmacological effects including antibacterial, antioxidant and immunomodulatory. This study aimed to investigate the effects of the long-term intake of low doses of DON and ZEN on growth performance and intestinal health of broilers, as well as the potential protective effect of supplementary Glycyrrhiza uralensis extract (GUE) in an 84-day feeding experiment. A total of 315 one-day-old male Liangfeng broilers were randomly assigned to three treatments: basal diet (CON), MOL diet (where 5% of corn in the basal diet was replaced with an equal amount of naturally moldy corn) containing DON and ZEN at 1.25 and 1.29 mg/kg, and MGUE diet supplemented with 0.1% GUE in the MOL diet. The MOL diet reduced the body weight (BW) of broilers at 56 and 84 day, body weight gain (BWG) and feed intake (FI) aged 1-56 and 1-84 days, and the feed conversion ratio (FCR) aged 1-84 days, as well as villus height (VH) and the villus/crypt (V/C) ratio, SOD and GSH-Px activities, and the expression of claudin-1, occludin and ZO-1, while increasing MDA level, the expression of TNF-α, IL-1β and IFN-γ in the jejunum of broilers. Additionally, MOL diet decreased the Firmicutes to Bacteroidetes (F/B) ratio and abundances of Lactobacillus (L.gallinarum and L.crispatus), and B.vulgatus, while increasing Bacteroides (B.fragilis and B.dore), Helicobacter (H.pullorum), and Escherichia (E.coli) in the ceca. In contrast, MGUE diet improved growth performance and returned it to a level comparable to that of the CON diet, increased VH and V/C ratio, SOD and GSH-Px activity, claudin-1, occludin and ZO-1 expression, while reducing MDA level, the expression of TNF-α, IL-1β and IFN-γ in the jejunum. Moreover, MGUE diet had a greater F/B ratio and abundance of Lactobacillus (L.gallinarum and L.crispatus) and B.vulgatus, while reducing Bacteroides (B.fragilis and B.dorei), Helicobacter (H.pullorum) and Escherichia (E.coli) in cecum. In conclusion, the long-term consumption of a low-dose DON-ZEN contaminated diet decreases growth performance and disrupts intestinal health and microbiota balance in broilers; however, dietary supplementation with GUE effectively mitigates the damage caused by DON-ZEN contamination.